(In) Segurança alimentar e COVID-19 no Amazonas: o caso da comunidade ribeirinha Nossa Senhora do Livramento na reserva de desenvolvimento sustentável do Tupé - Guimarães, Andréa Cristina (2024)
This study addresses food insecurity in the community of Nossa Senhora do Livramento, in Manaus, Amazonas, Brazil, located in the Tupé Sustainable Development Reserve, highlighting the complexities and challenges imposed by the COVID-19 pandemic. The research adopted a mixed methodological approach, employing both quantitative methods, through socioeconomic questionnaires, food frequency questionnaire, and the Brazilian food insecurity scale, as well as qualitative methods, through semi-structured interviews. The instruments were applied to one resident of each household in the sample that met the study's inclusion criteria. For this, a non-probabilistic sample was used utilizing the "Respondent-Driven Sampling" technique. This study allowed a comprehensive analysis of the community's food and socioeconomic conditions, revealing a multifaceted reality. The quantitative results indicated a high percentage of families at some level of food insecurity (78,6%), especially among those with lower family income, with families identified as in a severe situation of food insecurity having an average family income of 0.91 minimum wages (28,6% of the total). The qualitative interviews provided valuable accounts of the residents' personal experiences, their daily food possibilities, as well as the strategies developed and the impacts of the pandemic. In this sense, the conclusions point to a significant prevalence of food insecurity in the community, exacerbated by the health crisis, and which substantially reflects on the quality of life and food practices of that population. The work suggests that the implementation of such policies should take into account the cultural and socioeconomic specificities of the community, promoting food security while respecting local diversity and autonomy. The contribution of this study lies in its ability to articulate a detailed view of food insecurity in a pandemic context, offering empirical evidence that can guide targeted and effective interventions